The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/9958256
|View full text |Cite
|
Sign up to set email alerts
|

An IoT-Based Motion Tracking System for Next-Generation Foot-Related Sports Training and Talent Selection

Abstract: Motion tracking in different fields (medical, military, film, etc.) based on microelectromechanical systems (MEMS) sensing technology has been attracted by world's leading researchers and engineers in recent years; however, there is still a lack of research covering the sports field. In this study, we propose a new AIoT (AI + IoT) paradigm for next-generation foot-driven sports (soccer, football, takraw, etc.) training and talent selection. The system built is cost-effective and easy-to-use and requires much f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The experimental data revealed that the system can achieve an accuracy of about 80%. Lu et al [24] have developed a cost-effective system for the training and talent selection grounded on arti cial intelligence and the Internet of Things (AI + IoT). The proposed system can work on very less computational assets and can be employed in foot-driven sports.…”
Section: Dss For Action Recognition Of Track and Field Sports Using Acomentioning
confidence: 99%
“…The experimental data revealed that the system can achieve an accuracy of about 80%. Lu et al [24] have developed a cost-effective system for the training and talent selection grounded on arti cial intelligence and the Internet of Things (AI + IoT). The proposed system can work on very less computational assets and can be employed in foot-driven sports.…”
Section: Dss For Action Recognition Of Track and Field Sports Using Acomentioning
confidence: 99%
“…Although image analysis techniques can be used in the sports research field to make more accurate identification of athletes' behavior. However, this technology has some disadvantages in the development of the motion scene: the equipment cost is expensive, the system is vulnerable to the influence of the external environment, and relevant visual algorithms and image processing depend on a large number of hardware conditions [ 3 ]. With the popularity of IoT applications, sensor technology is developing rapidly, among which inertial microelectromechanical systems (MEMS) sensors are the most widely used.…”
Section: Related Workmentioning
confidence: 99%